Reproductive cycle, sexual maturity and fecundity of Nemipterus furcosus (Valenciennes, 1830) - Rahman, Mohammad Mustafizur; Samat, Amira F. (KeAi Communications Co., 2021)
Understanding the reproductive biology particularly sexual maturity, reproductive cycle and fecundity of fish is useful for fisheries management. Unfortunately, there is no information about reproductive biology of Nemipterus furcosus. This study addresses this deficit for N. furcosus. We conducted a 12-month study to understand the reproductive biology particularly the sex ratio, sexual maturity, fecundity and reproductive cycle of N. furcosus at the east coast of peninsular Malaysia. Results indicated that ratios of male and female were statistically similar up to 19.0 cm TL (total length). Male outnumbered female above 19.0 cm TL (p<0.05). The fecundity ranged between 30317 to 236938 with a higher fecundity in November-July compared to other months of the year (p<0.05). Male and female fish reached first sexual maturation at almost same size, 15.8 and 15.6 cm, respectively. This information is needed to determine the lowest acceptable harvest length of this fish under the management aim to enter female fish for reproduction minimum one time in their life. We estimated the reproductive period of N. furcosus applying oocytes diameter, histological examination of ovaries and monthly mean GSI. All these methods gave a consistent result about spawning season, which appeared to be from March to July with peaks in March and June. Based on this result, N. furcosus spawners can be protected during March to July for entering the reproductive stock. Apart from artificial breeding, the results of this study might facilitate future efforts at fine-tuning fishing effort for a proper management of N. furcosus both nationally and internationally.